Management of incidental pulmonary embolism - Klok, Frederikus A.; Huisman, Menno V. (The European respiratory journal, 2017)
Incidental pulmonary embolism (PE) is a frequent finding on routine computed tomography (CT) scans of the chest, occurring in 1.1% of coronary CT scans and 3.6% of oncological CT scans. Despite this high frequency, optimal management of incidental PE has not been addressed in clinical trials and remains the subject of debate. Although these CT scans have not been performed with a dedicated PE protocol and have suboptimal contrast enhancement, diagnosis of incidental PE has been shown to be accurate up to the segmental and subsegmental arteries. The embolic load in incidental PE is lower than that in symptomatic PE. Even so, observational studies suggest that the natural course of incidental PE is similar to that of symptomatic PE with regard to the risk of recurrent venous thrombotic disease and mortality. Interestingly, the increased use of more advanced CT technology has coincided with an increase in the rate of incidental subsegmental PE, as is the case for symptomatic subsegmental PE. Although clinical trials are lacking, and observational data are limited to cancer-associated incidental PE, the consensus is that the management of incidental PE is identical to that of symptomatic PE, including the choice of optimal drug class, outpatient treatment and total duration of treatment.